(untitled) (Pedagogical Horizons, 2019)
The article is based on results of a qualitiatv-empirical research with teachers to explore paradigms for sucessful (language) teaching in inclusive settings. It becomes obivious that all teacher need the utmost personal, social, systemic and diversity competences to deal with inclusion. Therefore the edcuation of teachers has to focus more than ever on the student him/herself